Effect of proton irradiation on mechanical properties of low‐density polyethylene/multiwalled carbon nanotubes composites. Issue 2 (19th February 2014) - Rui, Erming; Yang, Jianqun; Li, Xingji; Ma, Guoliang
<x xml:space="preserve">Abstract</x> The mechanical properties of low‐density polyethylene/multiwalled carbon nanotubes (LDPE/MWCNTs) composites without and with 170 keV proton irradiation were studied by tensile tests. Mechanisms of changes of mechanical properties were examined by means of small angle X‐ray scattering (SAXS), wide angle X‐ray diffraction (WAXD), Raman spectroscopy, and scanning electron microscopy (SEM). The tensile curve of LDPE exhibits three characteristic regions, while those for LDPE/MWCNTs composites only give the first and the second ones. The tensile curves of all samples with 170 keV proton irradiation have no obvious yield phenomenon. The addition of MWCNTs increases the ultimate tensile strength and decreases the elongation at break. Moreover, the ultimate tensile strengths of both LDPE and LDPE/MWCNTs composites with 170 keV proton irradiation are enhanced, and the elongations at break for them are decreased. Based on the analyses of SAXS, WAXD, Raman spectroscopy, and SEM, both the loading of MWCNTs and the proton irradiation can change the mechanical properties of LDPE/MWCNTs composites by a number of factors including the homogeneous distribution of MWCNTs in LDPE matrix, the aberrance zone between MWCNTs, and LDPE matrix, the interaction between MWCNTs and LDPE matrix, and the crystallinities of samples. POLYM. COMPOS., 36:278–286, 2015. © 2014 Society of Plastics Engineers